Hurst weighted random early detection algorithm based on self-similar traffic input - HUANG Li-ya; WANG Suo-ping (Tongxin xuebao, 2007)
RED as proposed by Floyd was based on the traditional Poisson input model,could not satisfy self-similar na-ture of network traffic.With this in view,an attempt has been made by proposing a modified RED algorithm,the HWRED algorithm with self-similar input.Modified RED algorithm can tune RED parameters according to the Hurst parameter of input traffic.Simulated results show modified algorithm increases evidently stability of queue size,and de-creases packet loss ratio,queue delay and queue delay variability,finally improves link use percentage of network.